Financial Performance Analysis and Z-Score Assessment Of Telecommunication Industry: PT Indonesia, PT XL Axiata, PT Indosat Ooredoo, PT Smartfren Telecom Before and After Covid19 Pandemic - Indriyanti Novitasari; Raden Aswin Rahadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The COVID-19 pandemic created changes in the telecommunications industry in Indonesia. During the pandemic, demand for digital services increased as people relied on online platforms for work, education, and daily activities. This led to an increase in demand for telecom companies. However, after the pandemic ended and people returned to normal physical activities, sales growth in the telecom industry began to decline. This study aims to understand the impact of COVID-19 on the financial performance of Indonesia's telecommunications industry, analyze the performance of each company, assess their risk of bankruptcy, and propose strategies to address these challenges. To achieve these objectives, quantitative approaches such as financial ratio metrics, including profitability, liquidity, solvency, and activity, were calculated. Statistical tests, including paired t-tests, Wilcoxon signed-rank tests, and Kolmogorov-Smirnov tests, were conducted to compare the financial performance of the Indonesian telecommunications industry before and after the pandemic. The Altman Z-Score model was also used to measure bankruptcy risk and identify whether the companies are in financial distress. The results showed a significant difference in Indonesia’s telecommunications industry’s financial performance before and after the pandemic in terms of profitability, as measured by ROA, ROE, and NPM, all of which showed an increase. Among the major players, PT Telkom Indonesia Tbk led the industry with strong and stable financial performance and was the only company classified in the